Arachnoid web: a mystery unravelled - Nair, Rohit R.; Sastry, Purushotham; Gurumurthy, B.; Kumar, Nandish K. C. (International Journal of Research in Orthopaedics, 2020)
A 47-year-old lady came with complaints of dull aching low backache and numbness over both the lower limbs since six months, aggravated since one week. She had tenderness over dorsal (D8-D10) and lumbar (L4-L5) spinal and paraspinal regions. Radiographs were inconclusive. Plain and contrast Magnetic resonance imaging (MRI) of the dorso-lumbar (D-L) spine with whole spine screening were also inconclusive initially. But close observation and serial viewing of all the sections revealed features of an arachnoid web at D7-D8 vertebral level. Patient underwent D7, D8 laminectomy with durotomy and arachnoid web excision. She had considerable improvement in her symptoms after the surgery. Hence, prompt recognition and early surgery ensure good outcomes in this uncommon yet relevant clinical entity.